CaSSIS color and multi-angular observations of Martian slope streaks. (December 2021) - Valantinas, A.; Becerra, P.; Pommerol, A.; Tornabene, L.L.; Affolter, L.; Cremonese, G.; Hauber, E.; McEwen, A.S.; Munaretto, G.; Pajola, M.; Bowen, A. Parkes; Patel, M.R.; et al.
Abstract: Slope streaks are albedo features that form frequently on equatorial Martian slopes. Most slope streaks are dark relative to surrounding terrains, a minor fraction is bright, and there are rare transitioning streaks that exhibit a contrast reversal partway downslope. Their formation mechanisms and physical surface properties are not well understood. New observations acquired by the Colour and Stereo Surface Imaging System (CaSSIS) on board ESA's ExoMars Trace Gas Orbiter (TGO) provide insights into slope streaks' surface microstructure, roughness and particle size ranges. Using multiple phase angle observations, we show that dark slope streaks are substantially rougher and possibly more porous than their bright counterparts, which are likely composed of more compact regolith. Color data acquired in the four wavelength bands suggest that dark streaks are spectrally similar to bright streaks but are composed of larger particles. The comparison of our orbital results to the laboratory measurements of Martian regolith analogs indicates that particles within dark slope streaks may be up to a factor of four larger than the granular material of the surrounding terrains. At one study site in Arabia Terra, using complementary imagery from other orbiters, we identify a case where dark slope streaks turned fully bright in a twenty-year period. These and CaSSIS observations suggest that bright slope streaks are old dark slope streaks, likely formed by deposition of dust or decomposition of surface aggregates into smaller particles. Graphical abstract: Image 1 Highlights: We report first CaSSIS observations of Martian slope streaks. We identified a site where dark streaks turned fully bright in a twenty-year period. Dark streaks are possibly composed of more porous and rough Martian soil. Laboratory measurements of Martian simulant indicate particle size effects. Bright streaks are more compact but of similar grain sizes relative to the surrounding terrains.